Acute lumbosacral nerve stimulation does not affect anorectal motor function in a rodent model. Issue 3 (26th November 2015) - Devane, L. A.; Evers, J.; Scott, M. S.; Knowles, C. H.; O'Connell, P.; Jones, J. F. X.
Abstract: Background: Sacral nerve stimulation has become a first line treatment for fecal incontinence, however, its effect on the motor function of the anorectum is uncertain. The aim of this study was to apply acute lumbosacral nerve stimulation in an animal model and to determine its effect on the external and internal anal sphincter forces, the rectoanal inhibitory and excitatory reflexes, and the slow wave frequency of the internal anal sphincter. Methods: Lumbosacral nerve stimulation was applied to 16 nulliparous female rats. A novel in vivo preparation was designed to allow simultaneous monitoring of external and internal anal sphincter forces. The effect of rectal distension on the two anal sphincters was also studied. Key Results: Lumbosacral nerve stimulation delivered at either S1 or L6 in rodents did not affect sphincter forces, rectoanal reflexes or slow wave frequency of anal canal smooth muscle. Conclusions & Inferences: The absence of effect on the motor pathways of continence suggests that the mechanism of action is predominantly on sensory feedback mechanisms from the anorectum, thereby increasing cortical awareness of the pelvic floor. Abstract : In a rodent model, acute sacral nerve stimulation does not affect internal or external anal sphincter motor function or rectoanal reflexes. This lack of action on the motor pathways of continence is in contrast to the known effects of SNS on sensory evoked cortical potentials and suggests that SNS works predominantly by increasing cortical awareness of the pelvic floor.